A review of adjudication in Malaysia, United Kingdom and Hong Kong construction industry / Azira Ibrahim, Zulhabri Ismail and Natasha Khalil - Ibrahim, Azira; Ismail, Zulhabri; Khalil, Natasha (2021)
Dispute is unavoidable in construction projects. The dispute may arise from the client or the contractor. This issue has been discussed over the years where the stakeholders try not to get involved in this matter. However, it is inevitable in construction projects and it can be regarded as endemic in the construction industry. To settle the dispute in construction contracts, there are two main categories which are public and private. Public dispute resolution refers to the nature of litigation which focuses on the fair implications of private interactions but open to the public. On the other hand private dispute resolution refers to a private mechanism where party autonomy will play a bigger role in dispute resolution and confidentially of the overall process. The objective of this study is to discuss the method of dispute resolution which focused on adjudication in Malaysia, United Kingdom (UK) and Hong Kong. The methodology of this study is qualitative. The information extracted from adjudication cases and a thorough study of literature review related to adjudication. The findings of this study are beneficial as the adjudication has increased gradually from year 2013 onwards and has become the main dispute resolution method between parties in the construction industry.